Designing the Performance Measurement System for A Digital Enterprise using Balanced Scorecard - Salsabila Katya Putri; Budi Sulistyo; Nanang Suryana (JTI: Jurnal Teknik Industri, 2024)
The main issue is the absence of a comprehensive KPI system to effectively measure the performance of digital products. Currently, the company PT XYZ unit tracks only two KPIs, such as revenue and total sales. This narrow focus overlooks aspects of achieving business success such as ensuring business fulfillment, business assurance, and employee competence in a growth and agile focus environment. As a result, performance targets are not fully met, and customer satisfaction declines in meeting service level agreements and service level guarantees. This research aims to fill these gaps by designing a performance measurement system using a Balanced Scorecard, and AHP is used for weighing the level of importance. Based on the research, the measurement system was developed, consisting of 7 Strategic Factors (SF), 9 Strategic Objectives (SO), and 12 KPI that are assessed on a quarterly basis. AHP analysis assigns the highest weight to financial perspective (56.60%), SF “market expansion and product innovation” (56.60%), SO “increase the revenue” (29.88%), and KPI “net profit margin growth” (26.72%). Once implemented, this system will standardize digital product performance measurement, aligning with company goals to drive revenue growth and operational efficiency. Keywords: BSC, AHP, KPI, Performance Measurement, and Digital Product